Unequal resource division occurs in the absence of group division and identity - Eliane Deschrijver; Richard Ramsey (Proceedings of the National Academy of Sciences, 2025)
Based on the seminal minimal group experiment, the widely influential social identity theory has, in the last 45 y, led to the belief that discrimination follows from intergroup relations and social identity. A large body of research evidenced that people discriminate against members of their out versus ingroup, even if groups and identities were assigned on the basis of a quantity estimate, aesthetic judgment, or a chance outcome. But to what extent may unequal resource division be accounted for by ad hoc difference versus sameness, outside of any group division? We show via Bayesian regression analyses in seven preregistered experiments (>1,400 subjects) that unequal resource division strategies persist against a single person that demonstrates a different versus the same quantity estimate, painting preference, or even coin flip (Experiments 1, 2, and 3ab), with 43.1% more money awarded for sameness relative to difference conditions (Experiments 4, 5, and 6). These findings open up the possibility that one key driver of discrimination may exist in a mechanism of interindividual comparison that treats ad hoc difference more negatively than ad hoc sameness. If unequal resource division readily emerges against a single person even after a mere chance difference, discrimination may be more widespread and occur for partly different reasons than is currently assumed. Theoretical implications for understanding cognitive and brain systems of discrimination are discussed.